Analisis kinerja keuangan pemerintah daerah sebelum dan setelah ditetapkannya keputusan menteri dalam negeri no. 29 tahun 2002 - Cici Dewi Sari Murni (IAIN Langsa, 2020)
This study aims to see whether there are differences in local government financial performance before and after the stipulation of Kepmendagri No.29 of 2002. This research was conducted in 12 districts/cities in Aceh which had not been expanded until 2001. The data used were secondary data with data collection techniques. documentation derived from the BPS in the Province of Aceh and other supporting sources. The variables used are the ratio of financial ability, ability to mobilize, level of dependency, and fiscal decentralization. Data were analyzed using parametric statistics which are different tests for two paired samples (paired sample t-test). The results showed that the financial performance of local governments in the form of financing ability, mobilization ability, level of dependency before the stipulation of Kepmendagri No. 29 of 2002 was not different from after the stipulation of Kepmendagri No. 29 of 2002, whereas in the form of fiscal decentralization before the stipulation of Kepmendagri No. 29 of 2002 is different from after the stipulation of Kepmendagri No. 29 of 2002.